390 Real World Analysis of Outcomes After Revascularization Surgery for Symptomatic Non-stenotic Carotid (SyNC) Artery Disease. (April 2023) - Madhani, Sarosh Irfan; Alvi, Mohammed Ali; Oushy, Soliman; Borg, Nicholas; Pando, Alejandro; Alotaibi, Naif M.; Savastano, Luis
Abstract : INTRODUCTION: Symptomatic non-stenotic carotid (SyNC) artery disease is emerging as one of the primary causes of embolic stroke of unknown source. The optimal secondary prevention strategies including medical therapy and revascularization (Carotid Endarterectomy (CEA) versus Carotid Artery Stenting (CAS)) continue to be controversial. METHODS: The National Surgical Quality Improvement Program (NSQIP) targeted dataset for CEA and CAS was queried for symptomatic patients with <50% stenosis of the ipsilateral carotid artery undergoing CEA and CAS between 2012-2019. Data analysis for continuous and categorical variables was carried out. RESULTS: A total of 363 symptomatic patients with <50% stenosis of the ipsilateral carotid artery were identified of which 22 underwent CAS and 341 underwent CEA. Statistical analysis showed that patients undergoing CEA were more likely to be male as compared to those undergoing CAS (68% vs 54.5%, p < 0.001). Additionally, patients in the CAS group were more likely to present with high-risk anatomy features compared to patients in the CEA group (31.8% vs 11.7%, p = 0.007) whereas patients undergoing CEA were more likely to have <50% stenosis contralateral ICA stenosis when compared to patients undergoing CAS (65.1% vs 36.4%, p = 0.001). Furthermore, patients undergoing CAS were more likely to experience post procedural stroke at 30 days compared to those undergoing CEA (13.6% vs 3.8%, p = 0.03). Upon multivariable analysis, CEA was associated with lower odds of post procedural stroke as compared to CAS (OR = 0.17, 95% CI 0.033-0.82, p = 0.027). CONCLUSIONS: Carotid revascularization for SyNC is being performed despite current guidelines and CEA is associated with lower odds of post-procedural stroke compared to CAS.